Pengaruh Sudut Kemiringan dan Kecepatan Putaran Saringan Pada Unjuk Kerja Mesin Pengayak Pasir Tipe Rotary - Cahyono, Andre Irawan; Qiram, Ikhwanul; Rubiono, Gatut (Virtual of Mechanical Engineering Article, 2019)
Sand is a noble material from homework, canals, fences, buildings, and various types of buildings or other constructions, almost all using sand material. So that sand sieving machines are needed in the sand separation process with various sizes needed. Based on this research, the Effect of Slope Angle on the Sieve Result can be affected. The best sieve results obtained at an angle of 10 ° with a weight of 1.35 kg fine sand, coarse sand yield 1.97 kg, and coarse sand yield of 2.68 kg and the Effect of Rotational Speed (Rpm), the best sieve time efficiency of sieving process results obtained 1.06 kg / s at variable angles of 20 ° and 50 rpm.